Single Fetal Death in Monochorionic Twin Pregnancy: Co-Twin Prognosis and Neonatal Outcome - Vale-Fernandes, Emídio (2017)
The incidence of single fetal death in twin pregnancy varies from 0.5% - 6.8%, leaving the surviving fetus with increased morbi-mortality. The prognosis is worse in monochorionic pregnancies. In addressing these cases it should be noted referral to tertiary center with differentiated perinatal support, induction of fetal lung maturation and termination of pregnancy if there’s loss of fetal well-being or possibility of maternal complications and suspected neurological sequelae in the surviving fetus. The risk of iatrogenic prematurity should always be weighed with the possible consequences arising from the fetus staying in a hostile uterine environment. The authors describe a case of a 32-year-old pregnant woman with monochorionic/diamniotic twin pregnancy diagnosed with death of one of the fetuses due to fetal growth restriction and velamentous insertion of the umbilical cord at 30 weeks of gestation. The couple opted for termination of pregnancy at 33 weeks after documentation of brain changes in the surviving fetus.